An Investigatory Project of Garlic (Allium sativum) and Lemongrass (Cymbopogon) as an Alternative Mosquito Repellent Spray: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Dengue is the fastest-spreading virus in the world, affecting up to 200,000 people per year andcausing 40,000 deaths through the bite of infected mosquitoes. The dengue virus spreads topeople when an infected mosquito bites them. About half of the world's population, or 4 billionindividuals, reside in dengue-risk regions. These mosquitoes, which can be found bothindoors and outdoors, prefer to bite humans. A person becomes infected after being bitten bya mosquito. Malaria is also spread by these mosquitoes.The results of this analysis in terms of ingredients, procedure, effectiveness, environmentalimpact, and presentation are Agree. The overall mean obtained by the chemical engineers is2.92, interpreted as Agree, while the dermatologists obtained an overall mean of 2.96,interpreted as Agree. The T-computed value is 0.706. T-critical is 3.355 with an alpha level of0.01 and degrees of freedom of 8, indicating there is no significant difference between the twogroups of respondents.The respondents recommended including extra vanilla in the ingredients and not boiling thegarlic during the procedure. More lemongrass should be added for greater efficacy. Try it withother insects to see how it affects the surroundings. Additionally, the presentation advises thatthe researchers utilize large bottles.
Keywords: Chemical Engineering